The Paradox of Limited Evidence and the Legitimacy of the Decision in the Ferdy Sambo Case - Gani, Maria Minerva; Tombeg, Meiraate Leos Lediana; Belo, Nimrod Welly; Palilli, Marchello Putra Toding (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The Paradox of Limited Evidence and the Legitimacy of Verdicts in the Ferdy Sambo Case reveals the gap between legal norms and the reality of criminal justice practice in Indonesia. This study originates from the background of evidentiary failure, which should serve as the core of judicial proceedings but was distorted by manipulation and obstruction of justice. The aim of the research is to analyze how the evidentiary system in the Indonesian Criminal Procedure Code, which adopts the negatief wettelijk bewijs system, failed to function properly in the Sambo case due to tampered evidence, pressured witnesses, and bureaucratic subordination. The research method employs a normative juridical approach with a case study, examining relevant legislation, doctrines, and court decisions. The findings show that although Indonesian law provides a comprehensive normative framework to guarantee justice through the 1945 Constitution, TAP MPR XVII/1998, the Criminal Procedure Code, the Penal Code, the Anti-Corruption Law, and the Judiciary Law, in practice the legal system remains vulnerable to abuse of power. The study concludes that the Sambo case is not only about premeditated murder but also reflects the fragility of evidentiary integrity and the legitimacy of judicial verdicts in the eyes of the public.